Andean Patriotic Epistemologies in the Martínez Compañón Codex - García Sudo, Alejandro (2017)
The bishop of Trujillo’s three-year-long pastoral visit to the northern realms of the Viceroyalty of Peru (1782-1785) was documented in the Martínez Compañón Codex, an intricately illustrated document. Musical notation contained therein remains a key reference for all those interested in Andean vernacular music. For many, the Codex’s songs and dances exemplify a history of cultural miscegenation and attest to the endurance of Pre-Columbian music. Other scholars add that the music’s stylistic hybridity could be read as a space of indigenous resistance or counterculture. The following essay shows how both of these premises are short-sighted and presents a third, less-familiar interpretation. The main argument is that the Codex’s music might have originated as expressions of nativist pride or patriotism that were sanctioned by the local authorities who sheltered the bishop during his visit. Andean leaders deployed a collection of aristocratic symbols and rituals to stake claims to legitimacy in times of political uncertainty. The essay suggests that several caciques collaborated with the bishop to that effect, and that the Codex’s music registered a shared desire to perpetuate ancient forms of colonial government, not annul them.